When is a little knowledge dangerous?: circumstances of recent heroin overdose and links to knowledge of overdose risk factors - Dietze, P.; Jolley, D.; Fry, C.; Bammer, G.; Moore, David (Elsevier Ireland Ltd, 2006)
Objectives: To describe the circumstances surrounding recent heroin overdose among a sample of heroin overdose survivors and the links to their knowledge of overdose risk. Methods: A cross-sectional survey of 257 recent non-fatal heroin overdose survivors was undertaken to examine self-reported knowledge of overdose risk reduction strategies, behaviour in the 12 h prior to overdose and attributions of overdose causation. Results: Most of the overdoses occurred in public spaces as a result of heroin use within 5 min of purchasing the drug. A substantial number of overdoses occurred with no one else present and/or involved the concomitant use of other drugs. While knowledge of at least one overdose prevention strategy was reported by 90% of the sample, less than half of the sample knew any single strategy. Furthermore knowledge of the dangers of mixing benzodiazepines and/or alcohol with heroin was associated with an increased likelihood of such mixing being reported prior to overdose. Conclusions: While heroin users can articulate knowledge of key overdose risk reduction strategies, this knowledge was not generally associated with a reduction in risk behaviours but was in some cases associated with increased reports of overdose risk behaviours. Further research is required in order to better understand this paradoxical effect, focussing on risk reduction education amenable to the social contexts in which heroin use takes place.